The Correlation of Social Support with Childbirth Readiness in Third Trimester Pregnant Women in Purwakarta Regency - Agustina, Rika; Rinawan, Fedri Ruluwedrata; Zulvayanti, Zulvayanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Social support and delivery readiness play a role in the process of adapting to the mother's role. Social support can prevent maternal mental health which can become negative during the perinatal period. The purpose of this study was to analyze the relationship between social support and delivery readiness in third trimester pregnant women in Purwakarta Regency. Methods: research using mixed methods with a concurrent embedded mixed-method strategy approach. The measuring instrument used a labor readiness questionnaire that had been tested for validity and reliability. Quantitative data retrieval technique using simple random sampling from 20 health centres in Purwakarta Regency was carried out randomly, taking 3 health centres and qualitatively by purposive sampling. The subjects of this study were pregnant women in the third trimester. Results: logistic regression analysis, namely the value of the R2 model (0.1732). Emotional support p (0.054), instrumental support p (0.274), informational support p (0.516). On the characteristics of the mother's age p (0.043). The results of the qualitative FGD and In-depth Interviews were influenced by aspects of antenatal care, service comfort, delivery experience, costs, education and social support. Conclusion: There is a relationship between social support, namely the dimensions of emotional support, age characteristics with delivery readiness in third trimester pregnant women in Purwakarta Regency.Dukungan sosial dan kesiapan persalinan berperan terhadap proses adaptasi peran ibu. Dukungan sosial dapat mencegah kesehatan mental ibu yang bisa menjadi negatif selama periode perinatal. Tujuan penelitian ini adalah menganalisis hubungan dukungan sosial dengan kesiapan persalinan pada ibu hamil trimester III di Kabupaten Purwakarta. Metode: riset menggunakan metode campuran dengan pendekatan strategi concurrentembedded mixed method. Alat ukur menggunakan kuesioner kesiapan persalinan yang sudah diuji validitas dan reliabilitas. Teknik Pengambilan data kuantitatif dengan simple random sampling dari 20 Puskesmas yang berada di Kabupaten Purwakarta dilakukan random diambil 3 Puskesmas dan pada kualitatif dengan purposive sampling. Subjek penelitian ini ibu hamil trimester III. Hasil: analisis regressi logistik yaitu nilai dari model R2 (0.1732). Dukungan emotional p (0.054), dukungan instrumental p (0.274), dukungan informational p (0.516). Pada karakteristik usia ibu p (0.043). Hasil FGD dan Indepth Interview kualitatif kesiapan persalinan dipengaruhi oleh aspek pemeriksaan kehamilan, kenyamanan pelayanan, pengalaman persalinan, biaya, edukasi dan dukungan sosial. Kesimpulan: Terdapat hubungan dukungan sosial yaitu pada dimensi dukungan emosional, karakteristik usia dengan kesiapan persalinan pada ibu hamil trimester III di Kabupaten Purwakarta.